2007
DOI: 10.1016/j.rmed.2007.06.029
|View full text |Cite
|
Sign up to set email alerts
|

The economic consequences of asthma among adults in Sweden

Abstract: The total costs of asthma for the society could be estimated at 3.7 billion SEK in the age range of 25-56 years, and thus approximately twice as high in the whole population of Sweden. The costs were strongly dependent on disease severity and increasing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
43
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 27 publications
6
43
1
4
Order By: Relevance
“…4 This is a challenge, as asthma is a complex disease in terms of both treatment and management and it generates high costs for society. 5 Modern asthma treatment emphasises asthma control, 6 and studies have demonstrated that it is possible for many patients to obtain satisfactory control. 7 However, there are also some reports of poor control for asthma patients in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…4 This is a challenge, as asthma is a complex disease in terms of both treatment and management and it generates high costs for society. 5 Modern asthma treatment emphasises asthma control, 6 and studies have demonstrated that it is possible for many patients to obtain satisfactory control. 7 However, there are also some reports of poor control for asthma patients in primary care.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma with more pronounced severity greatly affects daily life with an impaired quality of life, more frequent premature retirements and an increased risk of hospitalisation and death [1,5,6]. Severe asthma also causes the most significant economic burden of asthma, despite representing a minority of those with asthma [7,8].…”
mentioning
confidence: 99%
“…The two visible symptoms of asthma suggested by the physicians during the interviews were 'a need to stop for breathing when walking at own pace' and 'wakening at night with shortness of breath' (Pant 2008). Jansson et al (2007) based on his study in Sweden also reported shortness of breath and wheezing as the symptoms of asthma. Similarly, the visible symptoms of the eye disease were red eye, watery eye and light sensitivity.…”
Section: Smoking and Pet Ownershipmentioning
confidence: 95%